Optimization of Governance Factors for Smart City Through Hierarchical Mamdani Type-1 Fuzzy Expert System Empowered with Intelligent Data Ingestion Techniques - Fatima, Areej; Abbas, Sagheer; Asif, Muhammad; Adnan Khan, Muhammad; Saleem Khan, Muhammad (EAI Endorsed Transactions on Scalable Information Systems, 2019)
A Smart City is an urban area that uses the Internet of things (IoT) sensors to collect data and information to enhance the operational aptitude, in a way to manage assets and resources efficiently. Smart governance is a factor of a smart city for intelligent utilization of ICT to enhance the basic leadership. The smart government may be considered as a reason for creating smart governance, through the application of rising information and communication technology for administering. Smart Governance is totally dependent on the information that is being recorderded. Smart consists of multiple factors that an essential role in smart city activities, which require complex collaborations between governments, citizens and different partners. In this article, a new computational method is proposed for the evaluation of the Governance factors of the smart city using Hierarchical Mamdani Type-1 Fuzzy Expert System and empowered with fuzzy based data ingestion techniques.
Keywords: Product Inference Engine; Information and Communication Technology; Ubiquitous Sensor Networks; Internet of Things; Internet of Services; Internet of Energy; Internet of People